PRACTICES OF UNIVERSAL PRECAUTION TOWARD HIV AIDS TRANSMISSION AMONG HEALTH WORKERS IN PRIMARY HEALTH CARE SERVICES - Nurrochmah; Wahyuningsih, Taty; Nurrachmawati, Annisa (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The negative stigma against PLHIV held by health workers makes people reluctant to take HIV tests because they afraid of positive result and concerns about getting discriminatory services in primary health services Objective : this study aims to identify the universal precautionary practices of health workers in preventing HIV AIDS transmission in Primary Health Care Services. Research Methods/ Implementation Methods : Descriptive correlation study was a design of this study. Results : Health workers who have not received training on universal precaution are 73% Conclusion/Lesson Learned : Steps to create a supportive environment that emphasizes the importance of universal precautions can help reduce transmission HIV/AIDS toward health workers in Primary Health Care Services.